Extended Enterprise Metamodeling for Strategic Information System Alignment: Case Study - Falih, N.; Abouhilal, A.; ., . (International Journal of Engineering and Technology, 2018)
The enterprise meta-modeling is an important process for studying and managing organizations in order to improve their performance; it allows representing all views of the company for better governance. In this paper, we propose an extension of the ISO/DIS 19940 Meta-model by adding strategic constructs and specific tools from the Cobit framework. This extended meta-modeling allows a systemic and holistic analysis based on Galois lattices to intelligently drive the alignment of several components of the company. We also present a case study in a Moroccan transport company. We analyze a particular structural matrix to identify any relevant information that may contribute to process reengineering for Information System governance.Â Â